2011
DOI: 10.1111/j.1440-6055.2011.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviours of Diachasmimorpha kraussii (Fullaway) (Hymenoptera: Braconidae) and its host Bactrocera tryoni (Froggatt) (Diptera: Tephritidae) in a nectarine (Prunus persica (L.) Batsch var. nectarina (Aiton) Maxim) orchard

Abstract: Foraging behaviours of Diachasmimorpha kraussii (Fullaway) (Hymenoptera: Braconidae) and its host Bactrocera tryoni (Froggatt) (Diptera: Tephritidae) in a nectarine (Prunus persica (L.) Batsch var. nectarina (Aiton) Maxim) orcharda en_821 234..240 AbstractDiachasmimorpha kraussii is a larval parasitoid of dacine fruit flies. Host utilisation behaviour, including field foraging behaviour, is poorly known in this species. The diurnal foraging behaviour of D. kraussii and one of its common hosts, Bactrocera tryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…The lack of female sampling in the strawberry study is a weakness, but we do not think critically so for interpreting the data. A close correlation between male and female B. tryoni numbers has been previously demonstrated in field studies (Clarke and Dominiak 2010;Ero et al 2011) and was again found in the apple orchards. Thus, while the strawberry and apple studies show different patterns of fly distribution, we do not think it is because of sex-biased sampling.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The lack of female sampling in the strawberry study is a weakness, but we do not think critically so for interpreting the data. A close correlation between male and female B. tryoni numbers has been previously demonstrated in field studies (Clarke and Dominiak 2010;Ero et al 2011) and was again found in the apple orchards. Thus, while the strawberry and apple studies show different patterns of fly distribution, we do not think it is because of sex-biased sampling.…”
Section: Discussionsupporting
confidence: 78%
“…5), the answer to this may well be preferred resting sites. Bactrocera tryoni is known to spend a large percentage of its time resting (Weldon et al 2010;Ero et al 2011). While a preference for particular resting sites based on plant architecture has not been previously demonstrated for this species, it has for other tephritid fruit flies including Rhagoletis indifferens (Senger et al2009) and R. completa (Guill en et al 2011), Toxotrypana curvicauda (Aluja et al 1997) and several Bactrocera and Dacus species (Raghu et al 2004; et al 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There has been direct conflict in the literature on whether Bactrocera species have a resource, or nonresource, based mating system (for supportive papers of resource‐based mating systems see Drew & Lloyd, ; Drew et al ., ; for nonsupportive papers see Raghu et al ., ; Ero et al ., ). We found no evidence for a resource‐based mating system in our direct test which simultaneously offered “fruiting” and “nonfruiting” plants.…”
Section: Discussionmentioning
confidence: 77%
“…Gourmet premium). The two fruit types are both major hosts of B. tryoni (Hancock et al, 2000) and the wasp is known to orientate to both (Ero et al, 2011a;Ero & Clarke, 2012). All fruits had an average weight of 120 ± 10 g. Before use, fruit was wiped with a weak antifungal solution of nipagin 2.5 g/L water and then washed in tap water.…”
Section: Background and Commonalitiesmentioning
confidence: 99%